The Interest of School Children in Geographical Topics, Regions, and Working Methods–A Federal State Comparison between Bavaria and North Rhine-Westphalia - Hemmer, Ingrid; Hemmer, Michael (Journal of Geography Education, 2021)
Student interest is one of the most important prerequisites of geographical learning. This paper aims to explore whether there are significant differences between Bavarian and North-Rhine-Westphalian students’ interest based on factors, such as pedagogical approaches. The focus of the study presented in this paper is on student interest in geographical topics, regions, and methods and targets the identification of selected independent variables’ influence. A total of 1,400 students from Bavaria and North Rhine-Westphalia each participate on the survey completing a questionnaire that entailed slightly modified items of those already used during data collection in 1995 and 2005. The results showed that students from the two federal states displayed similar interest. Compared to the other variables, the federal state as a variable has the lowest influence.